Анализ сетей наземного цифрового вещания для стран со сложным рельефом местности - Халиль, Гассан (Eastern-European Journal of Enterprise Technologies, 2009)
The analysis of principles of construction of the systems of digital surface television and their basic descriptions which allow to be oriented at the decision of concrete questions of construction of the systems on the whole and choice of its technical parameters taking into account the feature of hypsography the Syrian Arabic republic is presented